Optimization of Supply Chain Management for Operational Efficiency in Beef Distribution - Hasmawati Hasmawati (JOURNAL OF SHARIA ECONOMICS, 2024)
The inefficiency in the beef supply chain poses significant challenges, including high logistics costs, product spoilage, and delays in distribution, which ultimately affect consumer satisfaction and business profitability. This research addresses the critical issues within the beef supply chain and explores strategies to enhance operational efficiency through optimized supply chain management (SCM). A qualitative research approach was employed, involving in-depth interviews with stakeholders such as cattle farmers, distributors, retailers, and logistics providers to identify pain points and inefficiencies. Observations were also conducted to analyze current practices in procurement, transportation, storage, and distribution of beef. The study revealed that a lack of coordination among supply chain actors, limited adoption of cold chain technology, and inadequate digital tracking systems significantly contribute to operational inefficiencies. By integrating best practices in SCM, including the use of cold storage transportation and digital inventory management systems, the research demonstrates the potential to reduce distribution times, minimize product losses, and lower operational costs. The findings emphasize the importance of collaboration among stakeholders and the adoption of technology to create a resilient and efficient supply chain. This study provides actionable recommendations for improving beef distribution, ensuring both quality and sustainability in meeting market demands.